Analyse und Bewertung des Elektrizitätssystems und des Wärmesystems der Wohngebäude in Deutschland - Merkel, Erik (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2018)
The present work investigates the evolution of the electricity system and the heat system of the residential buildings in Germany until 2050. The aim of the research work relates to the analysis of the temporal evolution of the investigated energy systems as well as of the potential of innovative technologies at the interface of electricity and heat along with the assessment of the goals of climate and energy policy in the heat system of the residential sector.